The Rationalization of the Highlanders’ Culture in the Terek Region of the Russian Empire in the Second Half of the 19th - Beginning of the 20th Centuries - Pokotilova, Tatyana Evgenevna; Rusetskiy, Mikhail Gennad`evich (Journal of History Culture and Art Research, 2017)
The article is devoted to the problem of constructing a new cultural identity of the highlanders living in the Terek region during the period of 1860-1917. In this article, the authors proceed from the established ideas in the science that the entire evolution of Russian history is filled with the practice of organizing the coexistence of different cultural identities in their constant interrelated development. The specific historical examples show how the inclusion of the Northern Caucasus in the Russian Empire, the modernization processes experienced by Russia itself during this period, the conscious acceptance of the elements of new consciousness, norms and values by the highlanders, has influenced the rationalization of the culture of the Terek region population. Such factors as kunachestvo, borrowings in the material culture, the provision of highlanders with economic and trade opportunities to work peacefully and provide their families with the results of peaceful work, the integration of highlanders into education and enlightenment on a modern basis have become effective means of creating a mechanism of interpenetration of the highlanders’ and Slavic cultures in the region and the formation of a new cultural identity of the North Caucasian highlanders.